Epidemiological Study of Clinical and Laboratory Profiles of Patients with Acute Lymphoblastic Leukemia at Dr. Soetomo Hospital Surabaya - Kezia Warokka Putri; I Dewa Gede Ugrasena; Yetti Hernaningsih (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: Considering the high number of acute lymphoblastic leukemia (ALL) and it being the type of cancer with the highest fatality rate among the children, this study seeks to determine the epidemiological description of the clinical and laboratory profiles of patients with ALL.Methods: This research used a descriptive study by using medical data record of patients with ALL. The research variables were gender, age, leukemia history of the patient’s family, nutritional status, symptoms and signs, laboratory examination, ALL subtypes, risk factors, and result outcomes. All data presented descriptively.Results: From a total of 50 patients, 54 % of them were male aged 1,5 – 10 years old. 84% of the patients’ family had no medical record related to leukemia. 42% of the patient malnutrition. Pale (78%), fever (64%), pain (32%), hepatomegaly (38%), lymphadenopathy (28%), splenomegaly (26%), patients with anemia (82%), leukocytosis (38%), thrombocytopenia (54%). The highest types were ALL–LI (68%), SR-ALL (54%), and remission outcome reached 82%.Conclusion: Insidence higher in male, aged 1,5 – 10 years old, malnourished at the start of the diagnosis. Most of the patients’ family had no medical history of leukemia. Symptoms and medical signs mostly appeared were pale, fever, and bone/joint pain. The physical examination showed hepatomegaly, lymphadenopathy, and splenomegaly and laboratory first test showed the patients had anemia, leukocytosis, and thrombocytopenia.